Patterns, Barriers and Facilitators of Responsiveness to Text Message Medication Reminders Among Youth Living with HIV in Southwest Nigeria - Mobolanle Balogun; Aniekan E. Ulor; Mayowa Odofin; Olufunmilola Idowu; Mmeli V. Chukwu; Abiola Aina; Oluwanifemi Adeshina; Hameed Adelabu; Lisa M. Kuhns; Amy K. Johnson; Kehinde M. Kuti; Nadia A. Sam-Agudu; et al. (Tropical Medicine and Infectious Disease)
The iCARE Nigeria study is evaluating a daily text message medication reminder intervention (TXTXT) to improve viral suppression and medication adherence among youth living with HIV (YLH), aged 15–24 years. In this sub-study, we evaluated text message responsiveness (text-back) at 24 weeks of the intervention as an indicator of engagement, as well as barriers and facilitators at one of six clinical study sites. Differences in responses by age group, birth sex, schooling status, education, mode of infection, and weekend/weekday and holiday/non-holiday periods were analyzed using t-test and multiple linear regression. Focus group discussions were conducted among three groups (low, average, and high text message responsiveness) and analyzed using a rapid content analysis approach. Overall, TXTXT responsiveness was 26.5% (4606/17,367); older age (18–24 years) and weekdays (versus weekends) were significantly associated with higher responsiveness. Facilitators included being comfortable receiving personalized text messages. Barriers included a lack of airtime and messages received late. Overall, text-back responsiveness to daily medication adherence messages among YLH was low, better among older participants, and higher on weekdays. Addressing barriers and promoting facilitators may improve responsiveness.